APPRECIATION OF ETHICS AND CIVILIZATION AS GENERAL COURSE IN MALAYSIAN UNIVERSITY: A LITERATURE REVIEW - Hon Shu Yee; Ahmad Johari Sihes (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The Appreciation of Ethics and Civilization Course is one of the new compulsory courses introduced in the 2019/2020 intake session for all public universities and private universities. This course is highly relevant for universities in Malaysia. Its sub-topics are organized around specific themes, addressing issues related to patriotism, ethics, and civilization on a global scale. Additionally, the course emphasizes the importance of tolerance in fostering harmonious relationships among the diverse ethnic groups in Malaysia. This course is recognized for fostering patriotism and encouraging good ethics in daily life, specifically aimed at university students in Malaysia. It also encompasses concepts similar to those discussed in the Ethnic Relations course. To enhance understanding of the course, it is essential to analyse several key aspects: objectives, content, human resources, teaching and learning methods, assessment methods, issues and challenges, as well as the moral values of implementation. Examining these elements will not only deepen comprehension of the course but also generate insights and suggestions for future research.